2003
DOI: 10.1002/ajmg.a.20189
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal detection of mosaic trisomy 1q due to an unbalanced translocation in one fetus of a twin pregnancy following in vitro fertilization: A postzygotic error

Abstract: Complete or mosaic trisomy for all of chromosome 1q has been seen rarely in a recognized pregnancy. A patient presented with twins following in vitro fertilization (IVF). Ultrasound showed twin A to have a diaphragmatic hernia, thick nuchal fold, and subtle intracranial abnormalities. Twin B appeared normal and a thick dividing membrane was seen. Amniocentesis of twin A showed a male karyotype with mosaic trisomy 1q in 57% of cells resulting from a translocation between chromosomes Yq12 and 1q12. Parental kary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…There are several previously reported CDH patients with duplication of 1q 39 40. Most of these duplications are the consequence of a balanced parental translocation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several previously reported CDH patients with duplication of 1q 39 40. Most of these duplications are the consequence of a balanced parental translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Kaufman et al (24) described a fetus whose ultrasound at 19 weeks showed an absent calvarium, large omphalocele, possible proboscis, and a suggestion of a VSD and whose karyotype was 46,XY/46,X,-Y,+der(Y)t(Y;1)(q12:q11) (24). Zeng et al (25) presented a twin following in vitro fertilization at 31 weeks' gestation. The karyotype of twin A was normal, while the others' karyotype was 46,XY/46,X,-Y,+der(Y)t(Y;1)(q12;q12) with left diaphragmatic hernia, hypoplastic lungs, a partial cleft palate, camptodactyly, syndactyly, ventriculomegaly, and hypoplastic cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…A 39-year-old G4P0121 at 13.1 weeks underwent CVS secondary to advanced maternal age. A transabdominal CVS was performed and yielded a mosaic unbalanced 1;20 translocation (46,XX,der(20)t(q12;p13) [16]/46,XX [4]; see Fig. 1), leading to trisomy of almost the entire long arm of chromosome 1 (1q) and partial monosomy 20p.…”
Section: Case Reportmentioning
confidence: 99%